Tinjauan Yuridis Pengawasan Perbankan Dan Perlindungan Nasabah Oleh Otoritas Jasa Keuangan (OJK) - Daffa Ramadhan; Anisha Nabila Firky; Jihan Khoirunnisa; Asqia Zahra Kalina; Ester Febrianti Sembiring; Qristiana Qristiana; Sri Juwita Putri; Farahdinny Siswajanthy (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The function of a bank is as a financial intermediary institution, namely as a bridge between fund owners and parties who need funds, both as depositors and borrowers. Bank-customer relationships often involve banking practices that have a negative impact on customers, but legal protection is often less than optimal. Because if you look at the relationship between banks and customers, banks have enormous control over banking transactions, and in some cases they control banking transactions. So that sometimes it is detrimental to customers. Based on the above facts, Law Number 21 of 2011 concerning the Financial Services Authority (UU OJK) has been promulgated. As a bank supervisory institution and as an institution that protects customer interests.